2019
DOI: 10.33972/jhs.161
|View full text |Cite
|
Sign up to set email alerts
|

LGBT Hate Crime: Promoting a Queer Agenda for Hate Crime Scholarship

Abstract: cursive (dis)acknowledgement and (dis)embodiment within criminological scholarship. NOTES 1. This is western nomenclature. Terms such as homosexual and gay do not apply to the cultural context of Samoa. Gynophilic and Androphilia are therefore used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…While engaging communities already involves strengthening the relationship between the researchers and the researched (Reynolds and Sariola, 2018; Wood et al, 2019), using participants’ own language is also reported to enhance communication and facilitate trust (Fritz and Vandermause, 2018; Nes et al, 2010). Still on the issue of language, Pickles (2019) suggests that scholars should incorporate the language of non-binary, fluid, and queer identities. As such, we used the term ‘litabane’, a term used and re-possessed by many LGBTQI populations in Lesotho (Matsúmunyane and Hlalele, 2019), to refer to sexually diverse individuals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…While engaging communities already involves strengthening the relationship between the researchers and the researched (Reynolds and Sariola, 2018; Wood et al, 2019), using participants’ own language is also reported to enhance communication and facilitate trust (Fritz and Vandermause, 2018; Nes et al, 2010). Still on the issue of language, Pickles (2019) suggests that scholars should incorporate the language of non-binary, fluid, and queer identities. As such, we used the term ‘litabane’, a term used and re-possessed by many LGBTQI populations in Lesotho (Matsúmunyane and Hlalele, 2019), to refer to sexually diverse individuals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…If you decide to wear a dress, those who know you are a lesbian will make sure that they tease you by calling you a man, so that everyone could pay attention to a man wearing a dress Being framed as attention seekers was a perception shared among many heterosexuals. The irony in this construct, as Pickles (2019) indicates, is that many people who share this sentiment are more concerned about gender presentation of the LGBTQI population, rather than their real sexuality. On the other hand, some participants reportedly indicated some social concerns regarding relationships with LGBTQI persons: I genuinely don't have any hard feelings towards them, and I still believe many people share the same sentiments, but what I know is that having a close relationship with them renders you to the same condemnation; people start questioning your own sexuality, and you also become an agent of societal attacks.…”
Section: Lgbtqi Population Are Sanctioned By Their Peersmentioning
confidence: 99%